Aprovechamiento de los residuos sólidos y líquidos de faenamiento del camal municipal y su incidencia en la disminución de la contaminación del río Tejar del cantón Otavalo. - Yacelga Pastillo, Sonia Magdalena (2014)
The present study had as general purpose waste of blood and rumen contents by slaughter processes the Otavalo municipal slaughterhouse, by designing an alternative treatment to reduce pollution at Tejar River. In the municipal slaughterhouse, during slaughtering activities, cattle organic waste blood and rumen contents that are generated in great quantities thereof that generating wastewater that are discharged into the Tejar River, which one creates an obvious environmental damage, and a waste resource that can be used or exploited. The methodology used is based on the observation direct techniques of the slaughter, interviews, photo capture, and laboratory analysis of wastewater samples. For wastewater analysis of 3 samples that were taken in 3 different days of weeks. The analyzed samples showed the presence of nitrogen in excess of 19mg / L, 15mg and 20mg / l each day. , And Biochemical Oxygen Demand BOD5 excess 140mg / l on the third day, so a higher concentration of organic matter was determined. The compost obtained showed a pH of 9.05, 17.37% moisture and nitrogen (N), phosphorus (P) potassium (K) of 1.06; 0.98 and 0.18 respectively, which all values are set to ideal values except potassium which ideal value is 1. Organic matter (OM), obtained 21.24% which is close to the minimum value required, and the C / N ratio 9.98 which is low compared to the minimum ideal. Therefore, the need to include other organic residue that provides an additional 5% to reach 15% ideal, and to avoid depression of nitrate was observed. In an interview with slaughterhouse workers, interesting and alternative methods were proposed to reduce the contaminating action of the slaughterhouse, including: use of vampire knife, using screens and channels, improving facilities and waste total collection before evacuating Tejar with water down the river. It was also suggested that an organic fertilizer with blood and rumen that can be collected from the slaughterhouse activities were. It was also mentioned that there would be other unofficially discharges pollutants to vote Tejar River by the textile and untreated sewage from the city. In conclusion, according to preceding arguments, making compost improved mix blood product, rumen, sawdust bay and forage (hay barley) constitutes the most appropriate proposal to leverage mentioned slaughterhouse waste and thus reduce the organic pollution of River Tejar generating an income for the sponsoring institution.